Highly selective synthesis of functionalized morphan derivatives through a multi-component cascade reaction of 3-formylchromones, 2-naphthols, and enaminones - Xinling Cao; Yinggang Duan; Kaihong Lv; Zihan Lu; Yihua Chen; Shengjiao Yan (Green Synthesis and Catalysis, 2023)
A novel protocol for the preparation of highly functionalized 2-azabicyclo[3.3.1]nonane (morphan) derivatives via a multicomponent cascade reaction, involving 3-formylchromones, 2-naphthols, and enaminones in the ionic liquid [BMIM]PF6 as the solvent and promoted by 1,8-diazabicyclo [5.4.0]undec-7-ene (DBU), was developed, which involved the cleavage of one C–O bond and formation of four bonds (1 ​C–O, 1 ​C–N, and 2 ​C–C bonds). As a result, a series of morphan derivatives were produced through a cascade reaction, including a sequence of 1,2-addition, enol-keto tautomerization, Michael addition, dehydration, another Michael addition, imine-enamine tautomerization, and N-alkylation reactions, which were accompanied by a ring-opening reaction. This protocol was suitable for combinatorial and parallel syntheses of natural product-like morphan compounds in a one-pot reaction rather than through tedious multi-step reactions.